The Effectiveness of Assertiveness Skills Training on the Self-Esteem of 14-Year-Old At-Risk Girls in Pishva County - Mirzaei, Parvin (Mental Health and Lifestyle Journal, 2024)
This study aimed to investigate the effectiveness of assertiveness skills training on enhancing emotional, social, academic, and general self-esteem among 14-year-old at-risk girls in Pishva County. The research employed a quasi-experimental design with a pretest-posttest control group. A total of 76 female students aged 14, enrolled in public middle schools in Pishva County during the 2024–2025 academic year, were randomly selected and assigned to either the experimental (n=38) or control (n=38) group. The experimental group received assertiveness training over six structured sessions, each lasting three hours. The control group received no intervention during the study period. Self-esteem was measured using the Coopersmith Self-Esteem Inventory, which assesses emotional, social, academic, and general dimensions. Data were analyzed using univariate analysis of covariance (ANCOVA) and SPSS version 16, with a significance threshold of α = 0.05. After controlling for pretest scores, ANCOVA results revealed statistically significant differences between the experimental and control groups across all dimensions of self-esteem. Emotional self-esteem showed a significant improvement in the experimental group (F = 6.698, p = .012), as did social self-esteem (F = 4.712, p = .033), academic self-esteem (F = 4.033, p = .048), and general self-esteem (F = 4.927, p = .029). The total self-esteem score also demonstrated a highly significant increase (F = 14.738, p < .001), indicating the overall efficacy of the assertiveness training. The findings support the conclusion that assertiveness training is an effective intervention for improving multiple facets of self-esteem in adolescent girls at risk. The intervention offers a valuable approach for educational and psychological settings aiming to empower youth in high-stress environments.